If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 1)(9x + -1) = 0 Reorder the terms: (1 + 9x)(9x + -1) = 0 Reorder the terms: (1 + 9x)(-1 + 9x) = 0 Multiply (1 + 9x) * (-1 + 9x) (1(-1 + 9x) + 9x * (-1 + 9x)) = 0 ((-1 * 1 + 9x * 1) + 9x * (-1 + 9x)) = 0 ((-1 + 9x) + 9x * (-1 + 9x)) = 0 (-1 + 9x + (-1 * 9x + 9x * 9x)) = 0 (-1 + 9x + (-9x + 81x2)) = 0 Combine like terms: 9x + -9x = 0 (-1 + 0 + 81x2) = 0 (-1 + 81x2) = 0 Solving -1 + 81x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 81x2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 81x2 = 0 + 1 81x2 = 0 + 1 Combine like terms: 0 + 1 = 1 81x2 = 1 Divide each side by '81'. x2 = 0.01234567901 Simplifying x2 = 0.01234567901 Take the square root of each side: x = {-0.111111111, 0.111111111}
| 5(-6X-7)=145 | | 16t^2+84t= | | 5(1+4y)=2(3+10y) | | 2(2-x)-(4-x)=-5 | | 2.5a-6=1.12a-1.86 | | x^2-15+x^2-36= | | 9(x+12)-4x=143 | | -3(w+5)+7=-23 | | 3x+1-5(x+1)=6x+3 | | -7(-6X-2)=-448 | | X(2x+1)=105 | | -2y=14 | | 7(2x-3)=3+5(3x-5) | | 75=3(-6m-5) | | 7(3+2X)=-49 | | 16t^2+122t= | | 0=-16t^2+15t+100 | | v^2-7v+6= | | 12x^2-13xy-14y^2=0 | | -3(4z+4)=4(3z-3) | | 3(m-4)+3=21 | | 24r+24(r+3)=408 | | 3(2-x)-5=4(x+2) | | -x^2(13x+9)-8x^2-25x^3= | | 6(8+4X)=240 | | i^2=x | | x-3=2x+18 | | 25-x/3=2x+7/4 | | .3(24w-18)=8w-6 | | 4(2X+10)=64 | | -2a+8+4a=7a-9a | | 2v^2-13v+15-v^2-6v-9= |